2017
DOI: 10.1589/jpts.29.1578
|View full text |Cite
|
Sign up to set email alerts
|

The treatment effect of hamstring stretching and nerve mobilization for patients with radicular lower back pain

Abstract: [Purpose] In this paper, hamstring stretching and nerve mobilization are conducted on patients with radicular lower back pain, and changes to pain levels, pressure thresholds, angles of knee joint extension, and disorder levels of lower back pain were studied. [Subjects and Methods] The subjects were divided into two groups: one group conducted hamstring stretches and was comprised of 6 male and 5 female subjects, and the other group received nerve mobilization treatment and was comprised of 5 male and 6 femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…While the addition of PNF stretching to the plan of care cannot be confirmed as contributing to the outcome, the report from the patient and desire to use the KIM regularly suggest PNF stretching enhanced recovery. Her response to the hamstring stretching is consistent with the findings of Lee and Kim 15 who reported improvements in pain, disability, and motion following a program of hamstring stretching in a cohort of adults being treated for low-back pain with radiating symptoms. The patients in their study performed an active knee extension while supporting their hip at 90°.…”
Section: Translation Opportunity To Patient Caresupporting
confidence: 83%
“…While the addition of PNF stretching to the plan of care cannot be confirmed as contributing to the outcome, the report from the patient and desire to use the KIM regularly suggest PNF stretching enhanced recovery. Her response to the hamstring stretching is consistent with the findings of Lee and Kim 15 who reported improvements in pain, disability, and motion following a program of hamstring stretching in a cohort of adults being treated for low-back pain with radiating symptoms. The patients in their study performed an active knee extension while supporting their hip at 90°.…”
Section: Translation Opportunity To Patient Caresupporting
confidence: 83%
“…In total, n = 914 participants were included. The smallest sample size was n = 22 (Lee & Kim 2017 ) and the largest n = 108 (Dwornik et al 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…The type of neural mobilisation technique and dosage varied amongst groups. The techniques used included slump (Ali et al 2015 ; Cleland et al 2006 ; Jain et al 2012 ; Jeong et al 2016 ; Karthikeyan, Jothikaran & Kiran 2014 ; Kirthika et al 2016 ; Malik, Kataria & Sachdev 2012 ; Nagrale et al 2012 ; Patel 2014 ; Rezk-Allah, Shehata & Gharib 2011 ; Tambekar et al 2015 ; Waleed 2015 ), SLR (Adel 2011 ; Ahmed et al 2013 ; Kaur & Sharma 2011 ; Malik et al 2012 ; Rezk-Allah et al 2011 ; Waleed 2015 ), bent leg raise mobilisation (Dwornik et al 2009 ; Patel 2014 ; Tambekar et al 2015 ) and neural mobilisations in side lying (Colakovic & Avdic 2013 ; Ferreira et al 2016 ; Lee & Kim 2017 ). One study reported a neural slider technique of the sciatic nerve involving the hip, knee and foot (Plaza-Manzano et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Like other studies males were from professions demanding labour with little time to give rest to their tiring bodies. (12,13,14). Indian population in general is prone to develop owing to its unhealthy life style, genetic makeup among other factors.…”
Section: Discussionmentioning
confidence: 99%
“…(11) Of the available treatments, Hamstring stretching and nerve mobilization both are effective in lumbar radiculopathy with nerve mobilization being accepted as superior method. (12) These techniques often require equipment, trained manpower and advances set ups, which patients coming in our OPDs cannot afford. Studies have documented in cases of nerve root compression the microcirculation is also compromised leading to nerve root oedema.…”
Section: Introductionmentioning
confidence: 99%